KONSTRUKSI SOSIAL BUDAYA MINANGKABAU ATAS PASAR - Damsar .; Indrayani . (Universitas Andalas, 2016)
One of the ethnicities most commonly found as a trader, merchant, or other seller at markets all over Indonesia, starting from Sabang to Merauke, was the Minangkabau people. Minangkabau people engaged in various activities of commerce or trade all goods needs. In addition Minangkabau people known for their culinary efforts, in particularly Padang buffet. An interesting question about it is how the Minangkabau people can present almost in all markets that exist in the archipelago? How social and cultural structures of the Minangkabau society form the market? As well as how the economic behavior of the Minangkabau people in relation to the market? To answer the above questions done field research with qualitative approach. Research data obtained from various sources such as in-depth interviews on various market actors and indigenous experts Minangkabau, observation of reality and literature on socio-cultural structures of the Minangkabau.The results showed that there is a qualitative relationship between socio-cultural structures of the Minangkabau, migration out ( merantau ) and markets. The market, culturally, is not separate from space Minangkabau people, because he was part of the prerequisites of the existence of a nagari. Migration out of the nagari or merantau is a cultural encouragement to become a useful person. One of the main roads traveled to become a useful person is to become entrepreneur, where the market is a place suitable for those options.